Perancangan Interior Sanrio Centre di Surabaya - Dewi, Ayu Rosdiana (Intra, 2013)
Along the development, the more advanced the technology world, especially in the entertainment world and the current popularity of people who liked the character of Sanrio in Surabaya also quite a lot. But unfortunately, there are no proper facilities to facilitate the activities of the lovers of the Sanrio characters. Interior design Sanrio Centre in Surabaya is a place of recreation as well as a forum for lovers of Sanrio characters. Here visitors can play while learning with information about the presence of Sanrio characters at the gallery and other facilities to support the interior using a Sanrio character more known to people at the feel of the interior. All contained in Sanrio Centre illustrates typical of Sanrio characters. Besides the lack of similar facilities in Surabaya, the facilities provided include galleries, cafes, shops, and learning and playing areas for childrens groups.